The Effect of Caffeine Ingestion during Evening Exercise on Subsequent Sleep Quality in Females - Ali, A.; O’Donnell, J. M.; Starck, C.; Rutherfurd-Markwick, K. J. (International Journal of Sports Medicine, 2015)
In a randomised, double-blind, placebo-controlled crossover design, 10 females taking monophasic oral contraceptives completed 90 min intermittent treadmill-running 45 min after ingestion of 6 mg∙kg−1 body mass anhydrous caffeine or artificial sweetener (placebo). Water (3 mL∙kg−1) was provided every 15 min during exercise. Venous blood samples were taken before, during and after exercise, as well as after sleep (~15 h post-ingestion), and levels of caffeine, paraxanthine, theobromine and theophylline were measured using high-performance liquid chromatography. Sleep quality was assessed using the Leeds Sleep Evaluation Questionnaire. Plasma caffeine concentration peaked 100 min after ingestion. Caffeine clearance was 0.95±0.14 mL·min−1·kg−1 while the elimination half-life of caffeine was 17.63±8.06 h. Paraxanthine and theophylline levels were significantly elevated at 15 h with no significant change in theobromine. Sleep latency and subsequent quality of sleep was impaired following caffeine supplementation (P<0.05); there were no differences between trials for how participants were feeling upon awakening. This is the first controlled study to examine caffeine supplementation on sleep quality in female athletes taking a low-dose monophasic oral contraceptive steroid following an intermittent-exercise running protocol. The data shows that female athletes using monophasic oral contraceptive steroids will have impaired sleep quality following evening caffeine ingestion.
Keywords: monophasic oral contraceptive; intermittent exercise; caffeine pharmacokinetics; caffeine metabolites; sleep quality; sleep latency